Quetiapine-associated and dose-related hypomania in a woman with schizophrenia - Atmaca, M; Kuloglu, M; Buyukbayram, A; Tezcan, E (Cambridge Univ Press, 2002)
[Abstract Not Available]
Keywords: quetiapine; hypomania; schizophrenia